â€œOsun Honeyâ€: Adichieâ€™s Half of a Yellow Sun from an African Sexuality Standpoint - Okeke, Ethel Ngozi (NIU Journal of Humanities, 2021)
Diverse critical commentaries have acknowledged the fuss over the pleasures of sex in Adichie’s Half of a Yellow Sun . In this novel, Adichie strikingly claims notice of sex, consequently shattering readers’ sense of convention through a radical departure from the rhetoric of reticence, indirection or shyness over sex matters – which had been the convention of African literary practice. Very significantly, Adichie succeeds in creating a style that is uniquely hers going by the evidence of her loud and clear erotic scenes, with full exposure of sexual details. Such a sensibility has been explained in the light of Western epistemic viewpoints or condemned, even, as an untoward influence of Western idiosyncrasies. This paper, however, seeks to explore Adichie’s aesthetics from a theory of African eroticism conceptualized as ‘osunality’, and as found in Yoruba divinity. Thus, this paper finds an approach such as this, from indigenous epistemology, relevant to the interpretation of what Adichie does with sex in the novel, especially as it pertains to her radical reconstruction of female sexuality. Keywords: Sexuality, Adichie, Yoruba divinity, African epistemology, eroticism, reticence.